2020
DOI: 10.1186/s13717-020-00227-8
|View full text |Cite
|
Sign up to set email alerts
|

Biomass and carbon stocks in mangrove ecosystems of Kerala, southwest coast of India

Abstract: Background Mangroves are important tropical carbon sinks, and their role in mitigating climate change is well documented across the globe. However, the ecosystem carbon stocks in the mangroves of India have not been studied comprehensively. Data from this region is very limited for providing sufficient insights and authentic evaluation of carbon stocks on a regional scale. In this study, we evaluated the ecosystem carbon stock and its spatial variation in mangroves of Kerala, southwest coast of India. Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(28 citation statements)
references
References 32 publications
3
23
2
Order By: Relevance
“…Indian mangroves host 46 true mangrove species, which represent about 56% of global mangroves species (Ragavan et al, 2016). Despite considerable work on the floristics and ecology, the inventory of carbon stocks in mangrove habitats of the Indian coast are scanty, and currently, only a few studies have reported the carbon stocks of these systems in Mainland India (Kathiresan et al, 2013(Kathiresan et al, , 2014Ray et al, 2013;Mitra & Gatti, 2015;Bhomia et al, 2016;Sahu et al, 2016;Suresh et al, 2017;Vinod et al, 2018;Gnanamoorthy et al, 2019;Banerjee et al, 2020;Harishma et al, 2020). Mangroves of the Andaman and Nicobar Islands (A & N Islands) are among the best in terms of density and growth in the country (Dagar et al, 1991;Mandal & Naskar, 2008;Ragavan et al, 2019) and accounts for an area of 616 km 2 ; out of which, 614 km 2 is in Andaman Islands with just 2 km 2 spread in Nicobar Islands (FSI, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Indian mangroves host 46 true mangrove species, which represent about 56% of global mangroves species (Ragavan et al, 2016). Despite considerable work on the floristics and ecology, the inventory of carbon stocks in mangrove habitats of the Indian coast are scanty, and currently, only a few studies have reported the carbon stocks of these systems in Mainland India (Kathiresan et al, 2013(Kathiresan et al, , 2014Ray et al, 2013;Mitra & Gatti, 2015;Bhomia et al, 2016;Sahu et al, 2016;Suresh et al, 2017;Vinod et al, 2018;Gnanamoorthy et al, 2019;Banerjee et al, 2020;Harishma et al, 2020). Mangroves of the Andaman and Nicobar Islands (A & N Islands) are among the best in terms of density and growth in the country (Dagar et al, 1991;Mandal & Naskar, 2008;Ragavan et al, 2019) and accounts for an area of 616 km 2 ; out of which, 614 km 2 is in Andaman Islands with just 2 km 2 spread in Nicobar Islands (FSI, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…A recent study also documented high carbon burial rates in the MCW and two other mangroves of the Ernakulam district (Rani et al, 2021). Another study also reported the high C storage capacity of the mangrove habitats in Kerala considering thirty sampling plots (Harishma et al, 2020). As there exists a large difference in the sedimentary carbon that was reported from the several mangrove stands of India, the present between seasons.…”
Section: Discussionmentioning
confidence: 86%
“…A recent study also documented high carbon burial rates in the MCW and two other mangroves of the Ernakulam district (Rani et al., 2021). Another study also reported the high C storage capacity of the mangrove habitats in Kerala considering thirty sampling plots (Harishma et al., 2020). As there exists a large difference in the sedimentary carbon that was reported from the several mangrove stands of India, the present study recommends the numerous mangroves patches (major and minor) present along the Indian coast, particularly along the Kerala coast, that were ignored in previous C studies, need to be assessed to completely understand the strength of Indian mangrove habitat sediments in holding C.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…For such wetland types, carbon stock values of 7.9 to 65 kg C m −2 were reported; differences in carbon stock are related with the depth of soil measured. Carbon stocks observed in Mexican mangroves soils were higher than the carbon stocks reported on tropical mangroves of Kerela, India (13.9 kg C m −2 ) [ 47 ], Sofala, Mozambique (15.9 kg C m −2 ) [ 48 ] and Honduran mangroves (5.7–10.6 kg C m 2 ) [ 49 ]. Despite its good storage of carbon in the soil of Mexican mangroves, its extent has decreased almost 55% from 1970 to 2018 (1,420,000 ha to 775,555 ha) [ 50 ], mainly by land use change or conflict between cattle ranches and fishermen in mangrove areas [ 51 ].…”
Section: Resultsmentioning
confidence: 99%